Differential Diagnosis of Parotid Lipoma in a Breast Ca Patient - Melda Misirlioglu; Yagmur Yilmaz Akyil; Mehmet Zahit Adisen; Alime Okkesim (Case Reports in Dentistry)
Lipomas are common benign tumors usually detected on the torso, neck, upper thighs, and upper arms. However, they are rarely found in the parotid gland region. Because of their rarity at this site, they are not often considered in the differential diagnosis of parotid tumors. This report describes a rare case of a lipoma in the superficial lobe of parotid gland. A 71-year-old female patient admitted to our department complaining about swelling and pain in the posterior area of the left mandibular region since one month. Her medical history included mastectomy after breast CA fifteen years ago. Clinical examination revealed a smooth-surfaced, soft, and painful mass, with well-defined margins in the left mandibular region. Differential diagnosis of metastasis, inflammatory neck swellings, and benign salivary gland tumors were considered for the patient. Advanced imaging methods such as ultrasonography and contrast tomography revealed that the lesion was a lipoma of parotid gland. A surgical intervention under general anesthesia was planned for the removal of the mass; however patient refused the surgical treatment. Patient was placed on six-month periodic recall. This article reviews the radiographic appearance and differential diagnoses of lipoma in this rare location.